2021
DOI: 10.1088/2631-7990/abdfd7
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the brittle–ductile transition in the extreme manufacturing

Abstract: The brittle–ductile transition (BDT) widely exists in the manufacturing with extremely small deformation scale, thermally assisted machining, and high-speed machining. This paper reviews the BDT in extreme manufacturing. The factors affecting the BDT in extreme manufacturing are analyzed, including the deformation scale and deformation temperature induced brittle-to-ductile transition, and the reverse transition induced by grain size and strain rate. A discussion is arranged to explore the mechanisms of BDT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 170 publications
0
25
0
3
Order By: Relevance
“…In this study a small subsurface microcrack was observed in 3Y125, reflecting the concentration of high stress at zirconia grain boundaries. However, the subsurface tensile component might well be sufficiently large to suffer a ductile-to-brittle transition of material removal mode in the blasting process [ 40 ]. When a critical tension accumulation was reached to initiate fracture within zirconia materials, there would be a collapse of the grain and an increase in the material defect, resulting in the reduced flexural strength [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study a small subsurface microcrack was observed in 3Y125, reflecting the concentration of high stress at zirconia grain boundaries. However, the subsurface tensile component might well be sufficiently large to suffer a ductile-to-brittle transition of material removal mode in the blasting process [ 40 ]. When a critical tension accumulation was reached to initiate fracture within zirconia materials, there would be a collapse of the grain and an increase in the material defect, resulting in the reduced flexural strength [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the obvious oblique cracks, the "4-C-A" test showed the largest surface roughness. The fracture surfaces of "1-M-A", "2-M-C", "5-A-C", and "6-A-M" test groups were very smooth, because of the intergranular fracture [36]. Even though the fracture section of "1-M-A" test has many long cracks, other zones were also very smooth.…”
Section: Roughness Of the Fractured Surfacementioning
confidence: 96%
“…For different kinds of ceramics, this scale is much less than 1 μm which is advantageous for the finishing but not for the high productive machining. Cutting at high speed promotes the reverse transition from ductile to brittle removal mode, which is useful in the processing of metals 17 …”
Section: Introductionmentioning
confidence: 99%
“…Reduction of surface defects is achieved through the use of special machining modes which provide the brittle-ductile transition induced by extremely small deformation scale or high temperature, and affected by the processing speed and cooling. 7,17 The transition from brittle to ductile removal mode leads to plastic deformations in thin processed layer and, as a result, smooth and crack-free surface. The main difficulty is to determine the correct machining mode, since the observed surface can be smooth while severe damage can occur in the subsurface layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation